Assessment of a new detection threshold for PM10 concentrations linked to African dust events in the Caribbean Basin. (1st March 2020) - Euphrasie-Clotilde, Lovely; Plocoste, Thomas; Feuillard, Tony; Velasco-Merino, Cristian; Mateos, David; Toledano, Carlos; Brute, France-Nor; Bassette, Céline; Gobinddass, Marieline
Abstract: The Lesser Antilles is an intermediate zone located between the Caribbean Sea and the Atlantic Ocean. This area is frequently affected by the major long range Saharan dust transportation from West African desert sources. The aerosols optical properties are provided by the AEronet Robotic NETwork (AERONET) measurement sites in Puerto Rico, Guadeloupe, and Barbados. Thus, Aerosols Optical Depth (AOD), Angstrom Exponent (AE), Volume Particle Size Distribution (VPSD), complex refractive indexes, and Single Scattering Albedo (SSA) were used to define the predominant type of atmospheric particles namely sea salt aerosols, mineral dust or aerosols mixture. Obtained results show that aerosols in the atmospheric column (AOD) and surface dust measurements ( P M 10 ) are well correlated with correlation coefficients of 0.72 and 0.81 respectively for Puerto Rico, and Guadeloupe. Detailed analysis of optical data associated to daily P M 10 concentrations highlighted that dust phenomenon can be observable below P M 10 threshold of 50 μ g ∕ m 3 given by the European directives to detect dust episodes. Indeed, for Caribbean islands, episodes of desert dust phenomenon have been detected from 35 μ g ∕ m 3 . The climatological assessment of monthly dust events observed in Puerto Rico, Guadeloupe, and Martinique between 2006 and 2016 highlighted a low dust season from November to February and a high dust season from May to August. Both seasons are separated by two transition dust periods: March to April and September to October. Lastly, the day-to-day back trajectories (NOAA-HYSPLIT) illustrated the general atmospheric circulation and show three main dust transportation routes: the North West African Path (62.7%); the South West African Path (20.8%) ; and the North East Atlantic Path (15.1%). By computing the average P M 10 concentrations bring from each path, we notice that South West African Path is the most loaded in mineral dust because he comes from one of the most persistently active and intense dust sources in the world, i.e. Bodélé Depression in northern Chad. Highlights: Microphysical characterization of aerosol particles in Caribbean islands is studied. Surface dust concentrations are linked to aerosol optical properties. A new PM10 threshold linked to African dust in the Lesser Antilles is proposed. General circulation of dusty air mass paths in the North Atlantic area is identified. Impact of desert dust phenomenon on vertical temperature profile is highlighted.